Effects of Limit Feeding Cold Stressed Growing Calves in the Morning Versus the Evening, as well as Bunk Line Sharing on Performance - C. A. Sasscer; S. P. Montgomery; C. I. Vahl; W. R. Hollenbeck; R. N. Wahl; A. J. Tarpoff; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:To determine the response of cold stressed growing calves to being fed in the evening instead of morning hours, as well as the effect of bunk line sharing. Study Description:Crossbred steers (n = 360) of Texas, Oklahoma, and Idaho origin were blocked by weight into four size groups and randomly assigned to pens, which were randomly allocated to one of five treatments. All steers received a diet formulated to provide 60 Mcal net energy for gain/100 lb of dry matter and were limit fed with a target of 2.0% of their body weight in dry matter intake. Treatments consisted of being fed in the morning (AM), in the evening (PM), fed half of their feed in the morning and half in the evening (50/50), and two treatments that allowed cattle to be fed in the same pen yet were rotated twice daily utilizing a holding pen, allowing for half of the calves to be fed in the morning (Shuttle AM) and half to be fed in the evening (Shuttle PM), doubling the use of the pen and bunk line. The steers were fed for 77 days and individual animal weights were taken on day -1 (allocation), day 0 (initial processing), day 64/65 (blood sampling), and day 77 (final weights). Plasma glucose was obtained individually on day 64 and 65, and pen weights were collected on days 0, 21, 28, 35, 56, 63, 70, and 77. The Bottom Line:When limit feeding cold stressed growing calves, neither shifting from morning feed delivery to evening feed delivery, nor bunk line sharing significantly improves the efficiency of feed conversion.
Keywords: Limit feeding; bunk line sharing; cold stressed calves